Hypertension and Stroke Pathophysiology and Management - Aiyagari, Venkatesh; Gorelick, Philip B.; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2011)
This timely volume addresses the intimate pathophysiologic relationship between hypertension and cardiovascular disease. Hypertension is one of the most important global public health challenges, and its relationship to stroke and other catastrophic cerebrovascular diseases is an area of growing understanding. In this outstanding book, the editors and authors clearly and concisely synthesize our developing knowledge and place epidemiologic and physiologic information into a practical clinical context. Comprehensive chapters present the evidence supporting strategies for stroke prevention and care, including blood pressure lowering therapies, anti-coagulation, and management of other cerebrovascular risk factors. In addition to prescriptive measures for first stroke prevention, the book illuminates current regimens for care immediately after acute stroke and for the prevention of recurrent stroke. A unique section is dedicated to the exploration of the interaction between elevated blood pressure and brain function and cognition. The concluding chapter provides a resource towards optimizing the organization of stroke care. Hypertension and Stroke is of great utility for specialists in neurology and cardiovascular medicine and a valuable practical resource for all physicians caring for older adults and hypertensive patients.
Keywords: Medicine; Family medicine; Internal medicine; Cardiology; Endocrinology; Nephrology; Neurology; Medicine & Public Health; Neurology; Internal Medicine; Cardiology; General Practice / Family Medicine; Nephrology; Endocrinology